Ideological and spiritual transformation: A critical discourse analysis of Dr. Bilal Phillips’ conversion journey using van Dijk’s model - Putra, Debi Akmalindo; Budiwati, Tri Rina; Husna, Mutiara; Afifah, Wiwiek (Journal of Religion and Linguistics, 2025)
This study examines the conversion narrative of Dr. Bilal Phillips using Teun A. van Dijk’s Critical Discourse Analysis (CDA) framework. Focusing on semantic structure, social cognition, and social context, the research draws data from a YouTube interview video titled “From Ex-Communist to Islamic Scholar.” The semantic analysis reveals presupposition, detail, and nominalization, while social cognition reflects person, self, and role schemas. The analysis of social context highlights the influence of power and access in shaping discourse. This study shows how digital narratives construct ideological shift and spiritual identities, offering insight into the persuasive power of discourse in religious transformation.